2010
DOI: 10.1016/j.neuron.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Misfolded Mutant SOD1 Directly Inhibits VDAC1 Conductance in a Mouse Model of Inherited ALS

Abstract: Summary Mutations in superoxide dismutase (SOD1) cause amyotrophic lateral sclerosis (ALS), a neurodegenerative disease characterized by loss of motor neurons. With conformation specific antibodies, we now demonstrate that misfolded mutant SOD1 binds directly to the voltage-dependent anion channel (VDAC1), an integral membrane protein imbedded in the outer mitochondrial membrane. This interaction is found on isolated spinal cord mitochondria and can be reconstituted with purified components in vitro. ADP passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
249
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(268 citation statements)
references
References 91 publications
12
249
0
Order By: Relevance
“…Ca 2+ -induced mitochondrial Ca 2+ uptake in permeabilized cells, which does not rely on ER Ca 2+ release or the intimate coupling between mitochondria and ER, was not affected in mutant SOD1 G37R cells. This finding is also consistent with the observation that mutant SOD1 does not affect VDAC1-mediated Ca 2+ transfer (Israelson et al 2010). Cytosolic ATP levels were also significantly decreased in mutant SOD1 G37R cells resulting in compromised ER Ca 2+ uptake in intact cells while ER Ca 2+ uptake in permeabilized cells provided with sufficient amounts of ATP was not affected.…”
Section: Mutant Sod1 May Affect Er-mitochondrial Couplingsupporting
confidence: 90%
See 2 more Smart Citations
“…Ca 2+ -induced mitochondrial Ca 2+ uptake in permeabilized cells, which does not rely on ER Ca 2+ release or the intimate coupling between mitochondria and ER, was not affected in mutant SOD1 G37R cells. This finding is also consistent with the observation that mutant SOD1 does not affect VDAC1-mediated Ca 2+ transfer (Israelson et al 2010). Cytosolic ATP levels were also significantly decreased in mutant SOD1 G37R cells resulting in compromised ER Ca 2+ uptake in intact cells while ER Ca 2+ uptake in permeabilized cells provided with sufficient amounts of ATP was not affected.…”
Section: Mutant Sod1 May Affect Er-mitochondrial Couplingsupporting
confidence: 90%
“…Mutant SOD1 has been shown to associate with Lysyl-tRNA synthetase (Kawamata et al 2008), an enzyme required for mitDNAencoded protein translation, members of the Bcl-2 family of proteins and the voltage-dependent anion channel VDAC1 (Israelson et al 2010). The binding of mutant SOD1 to VDAC1 deserves further attention.…”
Section: Mutant Sod1 May Affect Er-mitochondrial Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial abnormalities have been identified in postmortem tissue derived from ALS patients, 24 with ALS-linked SOD1 mutations shown to associate with mitochondria and disturb their bioenergetic capacity through an interaction with VDAC1. 25 In vivo autoradiography studies in SOD1 mice have also demonstrated that glucose utilization is impaired in motor tracts before any pathologic alterations and that this is accompanied by ATP depletion. 26 Metabolic alterations favouring lactacidosis may also be triggered directly as a consequence of Ca 2 þ -mediated excitotoxicity and glutamate excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In SOD1 G93A mice, a mouse model of familial ALS, mutant SOD1 protein accumulates in mitochondria early during disease (Luo et al 2013, Deng et al 2006, Higgins et al 2002. This build up of mutant protein is suggested to impair mitochondrial function (Song et al 2013, Israelson et al 2010, Pasinelli et al 2004. In line with these findings, mitochondria had a metabolic switch from oxidative phosphorylation to glycolysis in transgenic SOD1 G93A mice, NSC34 cells (motor neuron-like cell line) and fibroblasts transfected with mutant SOD1 compared to controls (Mattiazzi et al 2002, Richardson et al 2013, Allen et al 2013.…”
Section: Introductionmentioning
confidence: 92%